9x-4=5(2x-3)

Simple and best practice solution for 9x-4=5(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4=5(2x-3) equation:


Simplifying
9x + -4 = 5(2x + -3)

Reorder the terms:
-4 + 9x = 5(2x + -3)

Reorder the terms:
-4 + 9x = 5(-3 + 2x)
-4 + 9x = (-3 * 5 + 2x * 5)
-4 + 9x = (-15 + 10x)

Solving
-4 + 9x = -15 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-4 + 9x + -10x = -15 + 10x + -10x

Combine like terms: 9x + -10x = -1x
-4 + -1x = -15 + 10x + -10x

Combine like terms: 10x + -10x = 0
-4 + -1x = -15 + 0
-4 + -1x = -15

Add '4' to each side of the equation.
-4 + 4 + -1x = -15 + 4

Combine like terms: -4 + 4 = 0
0 + -1x = -15 + 4
-1x = -15 + 4

Combine like terms: -15 + 4 = -11
-1x = -11

Divide each side by '-1'.
x = 11

Simplifying
x = 11

See similar equations:

| 3x+4x=-x+7m | | -1.2y+.8=-.76 | | 7x+1=2(2x+2) | | 44+m=35 | | h(t)=-16t^2+122t+10 | | 6x-1=4(x-1) | | 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) | | 8n-12=40 | | (7+x)/2+3=12 | | 155*22/31*18/25 | | 5a-12=88 | | 9/8*4/5 | | 12-(4m+4)=3+3m-16 | | 2(x-5)+1=-(x+3) | | 7x-24=54 | | -2*(3x-1)-3=-4 | | -0.5x+4.21=0.3x+8.41 | | 6/7*14/27*9/10 | | x-2/3=5-x/2 |

Equations solver categories